The Effect of Jet Angle and Initial Plate Temperature during Jet Impingement Heat Transfer Process in Ultra‐Fast Cooling Technology. Issue 5 (29th September 2014) - Xie, Qian; Wang, Bingxing; Wang, Zhaodong; Wang, Guodong
<x xml:space="preserve">Abstract</x> Thermo‐mechanical control process (TMCP) technology is widely used for processing steels, where an important aspect is controlled cooling, Recently, the ultra‐fast cooling (UFC) method, which has high flow speed, adjustable inclination angle, and stagger arranged nozzles is gradually replacing the traditional cooling practice. This paper focuses on the flow field and heat transfer mechanism in high temperature plates during the cooling process. Next, the effect of different initial temperatures (600 and 750°C) and inclination angles (0°, 30°, and 60°) were studied. The surface temperature and heat flux were calculated using finite difference method. The data suggests that with the initial temperature increasing from 600 to 700°C, and the inclination angle increasing from 0° to 60°, the maximum heat flux and its corresponding temperature increases in the major part of the cooling region. Given that the experimental conditions were similar to the industry, the new findings are expected to effectively guide the development of UFC in the near future.